How to Facilitate Adherence to Cardiac Rehabilitation in Primary Health Settings for Ischaemic Heart Disease Patients. The Perspectives of Health Professionals - Ravn, Maiken Bay; Uhd, Maria; Svendsen, Marie Louise; Ørtenblad, Lisbeth; Maribo, Thomas (Frontiers in Rehabilitation Sciences, 2022)
Background Cardiac rehabilitation (CR) is a class 1A recommendation and an integrated part of standard treatment for patients with cardiac disease. In Denmark, CR adheres to European guidelines, it is group-based and partly conducted in primary health settings. Despite high evidence for the benefits of CR, it remains underutilised. How to facilitate CR adherence in primary health settings is poorly understood. Aim This study explores health professionals’ perspectives on how to facilitate CR adherence for patients with ischaemic heart disease in primary health settings. Methods Data were collected through focus group discussions. Respondents were health professionals specialised in and working with CR in primary health settings. Data were analysed using thematic analysis. Results Eleven health professionals participated in two focus group discussions. Five themes emerged as facilitators of CR; (1) placing the person at the centre, (2) coherent programme, (3) flow of information, (4) context, and (5) sense of community. Conclusion This study illuminates the complexity of facilitating adherence to CR in primary health settings and provides ways in which health professionals may facilitate adherence. Placing the person at the centre is pivotal and may be done by adapting CR offers to patients' social context, culture and life circumstances and ensuring a sense of community. The rhetoric related to CR should be positive and throughout the entire course of treatment health professionals should possess a generic and collective approach to and view of CR. Perceiving these elements as potential facilitators is of vital importance and addressing them may facilitate adherence.